PENGARUH PELATIHAN SERVICE EXCELLENT UNTUK MENINGKATKAN PELAYANAN PERAWAT YANG BERORIENTASI PADA KEPUASAN PASIEN DI RUMAH SAKIT - , Nia Kusuma Wardhani, S.Psi., Drs. Fathul Himam, MPSi., MA., Ph.D., Psi. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Service excellent is an important factor to increase patient satisfaction. Patients have desire to get good service, cared and needs met. In addition service excellent has contribution in increasing patient visit. This research was intended to improve nurse behavior oriented on patient satisfaction in hospital. The increase in nurse behavior oriented on patient satisfaction is expected to be capital in implementing service excellent in hospital. The research used quasi experiment method with pre post test control group design. Subjects were assigned into two groups: experiment group (get treatment) of 17 persons and control group (non treatment) of 17 persons. Subjects were nurse working at Klaten Hospital. Training was carried out in four sessions of 3-4 hours each. Evaluation of training results was done three weeks after training and follow up was given six weeks after training. Instrument used to measure service excellent was based on dimension developed by Parasuraman, Zeithmal, and Berry (1988), consisting of tangible, reliability, responsiveness, assurance and empathy. Data analysis used in this research was t-test. Results indicated that change in score from pre test to post test in both groups (experiment and control) was significantly different at t=3,080